2011
DOI: 10.1289/ehp.1002848
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Complex Pathogenic Effects of Dioxins and Polychlorinated Biphenyls in Obese Subjects before and after Drastic Weight Loss

Abstract: BackgroundIn humans, persistent organic pollutants (POPs) are stored primarily in adipose tissue. Their total body burden and their contribution to obesity-associated diseases remain unclear.ObjectivesWe characterized POP total body burden and their redistribution in obese individuals before and after drastic weight loss and compared these values with a variety of molecular, biological, and clinical parameters.MethodsSeventy-one obese subjects were enrolled and underwent bariatric surgery. Blood and adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
141
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(155 citation statements)
references
References 29 publications
7
141
1
6
Order By: Relevance
“…As mentioned before, moderate or severe weight loss was associated with increased plasma levels of POP, like PCB and organochlorine pesticides (13)(14)(15). e increased plasma levels of POP induced by weight loss are also correlated to changes in adipose POP.…”
Section: Adipose Tissue: the Source And Target Of Endocrine Disruptinmentioning
confidence: 70%
See 3 more Smart Citations
“…As mentioned before, moderate or severe weight loss was associated with increased plasma levels of POP, like PCB and organochlorine pesticides (13)(14)(15). e increased plasma levels of POP induced by weight loss are also correlated to changes in adipose POP.…”
Section: Adipose Tissue: the Source And Target Of Endocrine Disruptinmentioning
confidence: 70%
“…e increased plasma levels of POP induced by weight loss are also correlated to changes in adipose POP. Some researchers investigated POP concentrations in blood and adipose tissues and also assessed the total amount of fat mass (30). eir results indicated that the POP concentration in the adipose tissue increased with weight loss, this being correlated with the signi cantly decrease of the total amount of fat mass.…”
Section: Adipose Tissue: the Source And Target Of Endocrine Disruptinmentioning
confidence: 99%
See 2 more Smart Citations
“…At least 17 dioxins/furans and 18 polychlorinated biphenyl congeners accumulate in different adipose tissue depots. 7 Drastic weight loss induced by gastric bypass (GBP) led to increased levels of serum persistent organic pollutants and, within 6 to 12 months, to a significant 15% decrease in total polychlorinated biphenyls. In this study, persistent organic pollutants levels were positively correlated with liver toxicity markers and lipid parameters.…”
mentioning
confidence: 99%